Bioinoculants and organic soil amendments affect nematode diversity in apple orchards - Olimi, E.; Bickel, S.; Wicaksono, W.A.; Kusstatscher, P.; Coyne, D.; Weber, B.; Cernava, T.; Berg, G. (Elsevier, 2023)
Nematodes with their versatile lifestyles provide a suitable lens to decipher the conditions of agroecosystems, but less is known about how they are affected by bioinoculants and organic soil amendments. To test if treatments modify the nematode community, we studied nematode communities in two different apple orchards under organic and integrated farming. Soil was treated with products containing arbuscular mycorrhizal fungi, bioeffectors, and organic amendments. The comparison between baseline and control samples indicated an overall higher nematode richness in organic than the integrated orchard. Sampling time more than treatment had a significant effect, and higher community richness was observed during spring as compared to autumn. The variation in nematode community composition was mainly explained by sampling time followed by treatment, and orchard type. Although all treatments reduced nematode richness, their effect generally varied across treatments. In both orchards, season-dependent effects of treatment on nematode families and trophic guilds were observed, with a higher percentage of bacterivorous and lower percentage of herbivorous nematodes during spring. The effect was driven by a few families, i.e. Rhabditidae and Tylenchidae. Our study provides insights about the effect of soil treatment on nematodes with implications for the development and modification of bioinoculants.